PENGARUH PENGGUNAAN MEDIA PREZI TERHADAP HASIL BELAJAR SENI RUPADI SMA N 9 PADANG - NOVI WANDARI, Drs. Abd. Hafiz, M.Pd, Yofita Sandra, S.Pd., M.Pd (Serupa The Journal of Art Education, 2015)
The purpose of this research is to investigate the effect of prezi learning media toward student’s learning outcome in arts and culture subject at grade XI of SMAN 9 Padang. This research is quasi experiment al research and the technique of selecting sampling. Research finding shows that there is an effect of prezi program toward students’ learning outcome of arts and culture subject at grade XI of SMAN 9 Padang. Based on t-test calculation, thitung = 16.703 and ttabel = 1.694, it means that thitung > ttabel thus there is a positive effect in using prezi learning media toward students’ learningoutcome of arts and culture subject at grade XI of SMAN 9 Padang.Kata Kunci : Media pembelajaran, Prezi, Hasil Belajar, Seni Rupa